High antioxidant - and anthocyanin contents of sour cherry cultivars may benefit the human health: international and Hungarian achievements on phytochemicals - Veres, Zs.; Holb, I. J.; Nyéki, I. J.; Szabó, Z.; Remenyik, J.; Fári, M. G. (International Journal of Horticultural Science, 2006)
Evidence suggests that a diet with high fruit and vegetable consumption may decrease the risk of chronic diseases, such as cardiovascular diseases and cancer, and phytochemicals including phenolics, flavonoids and carotenoids from fruits and vegetables may play a key role in reducing chronic disease risk. Recent research has proved that sour cherry (Prunus cerasus L.) is a valuable natural source of some bioactive compounds important in human health preservation. According to the published data, the most important biological effects of sour cherry are connected — directly or indirectly — to their endogenous antioxidant behaviour as well as to their specific pattern of anthocyanin components. In the present work, we measured the total antioxidant capacity of some Hungarian sour cherry varieties in combination with their anthocyanin-, and vitamin-C content. In 2003, twelve clones were selected and grafted from a local sour cherry population called "Bosnyák" sour cherry grown in small home gardens and farms of the village Csengod (Great-Plain Region, South Hungary). Other Hungarian sour cherry varieties, i.e. cv. Újfehértói fürtos, cv. Érdi bőterrnő, cv. Debreceni bőterrnő, cv. Csengődi and cv. Kántorjánosi served as a control.